Legal Consequences of Offenders Possessing and Controlling Bomb Explosives Without Rights and Without Permits (Verdict 1107/Pid.Sus/2020/Pn.Tjk) - Bambang Hartono; Zainudin Hasan; Nurul Shyashya (Universitas Negeri Semarang, 2022)
The manufacture of low explosives without a permit is very dangerous. Not only with a permit that has been set more than the level of security of the explosives. This attack on the manufacture of low explosives without a permit has been formulated in the Emergency Law no. 12 of 1951 concerning Firearms and Explosives. This type of research used normative juridical and empirical juridical methods. Results Based on the research and discussion, it is known that the Investigation Process in the case of the Crime of Possessing Unauthorized and Unlicensed Bomb Explosives is in accordance with the Investigation Procedure according to the elements contained in the criminal act, namely Whoever, Investigation, Investigation, and Arrest. The process of proof in terms of proof is one of the important elements in criminal procedural law which determines whether or not a trial is guilty. Legal Consequences of the Crime of Possessing Unauthorized and Unlicensed Bomb Explosives based on evidence in court.